Pressuring MPs to act: parliament, organized interests and policymaking in Uganda and Tanzania. Issue 4 (19th May 2021) - Collord, Michaela
ABSTRACT: What motivates MPs to challenge executive policy priorities? When and why do they support seemingly more "pro-poor" measures? This article presents a novel framework to answer these questions, adapting its analysis to the context of competitive authoritarian regimes in Africa. Recent literature tends to focus on whether heightened electoral pressure encourages more pro-poor policy interventions, for instance, leading to improved health services. While not dismissing the significance of voter demands, this article refocuses attention on the largely overlooked role of organized interests in shaping legislative action. More specifically, it examines how the distribution of power across more "mass-based" groups as well as within the ruling elite jointly influence policy outcomes, including pro-poor policies consonant with voter preferences. The argument is two-fold: one, mass-based groups – unions, farmers' associations and the like – can help galvanize MPs to demand more pro-poor policy; two, elite divisions, especially within the ruling party, help create the opening for activists to lobby effectively. Using a process-tracing methodology, the article demonstrates this theory through two case studies of semi-successful legislative interventions in Uganda and one failed attempt in Tanzania. For evidence, it draws on a mix of elite interviews, party and parliamentary reports, and press reviews.